Application of Fluorescent Dyes to Assess the State of Bovine and Equine Erythrocytes after Cryopreservation - Ulizko, Pavlo Yu.; Bobrova, Olena M.; Vodopyanova, Larisa A. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 189